Climate Change Adaptation: New Vistas for Management Research - Benischke, Mirko H.; D’Ippolito, Beatrice; Sharma, Garima; Wickert, Christopher (Journal of Management Studies, 2025)
Abstract Climate change adaptation has for a long time been the neglected half of the climate equation, as most attention has been directed toward mitigation. Yet, the catastrophic effects of a changing climate are already occurring, unavoidable, and in many cases irreversible. Organizations need to identify ways of adapting to present and future climatic conditions. In this editorial, we make the case for climate change adaptation as a research topic on par with mitigation. We outline how and why management and organizational scholarship should work toward an integrated approach of mitigation and adaptation in responding to climate change, suggesting three key avenues of research for future inquiry. In so doing, we encourage more impactful and ecologically relevant management research that will make a difference to society at large.